Cutaneous involvement by colonic extranodal NK/T-cell lymphoma mimicking mycosis fungoides: A case report - Panitta Sitthinamsuwan (2018)
We report a 51-year-old woman with cutaneous involvement by extranodal NK/T-cell lymphoma (TCL) of the colon that microscopically mimicked mycosis fungoides (MF). She had a history of fever of unknown origin for 2 months and then developed multiple erythematous papules on her trunk and extremities. A skin biopsy revealed superficial infiltration by atypical small to medium-sized lymphocytes with epidermotropism and Pautrier collections. Immunohistochemical studies showed expression of CD3 and TIA-1 with lack of expression (double negative) of CD4 and CD8. Initially, we reported the diagnosis as MF, cytotoxic variant. Thereafter, computerized tomography scan incidentally identified a colonic mass. A colonic biopsy revealed infiltration of atypical lymphoid cells with the same morphology and immunophenotype as those found in the skin. Additionally, CD56 and Epstein-Barr virus-encoded RNA in situ hybridization in both skin and colonic biopsies were diffusely positive. Thus, extranodal NK/TCL was diagnosed. Delta T-cell receptor (TCR) gene rearrangement was documented in the skin biopsy by polyacrylamide gel electrophoresis and fluorescence capillary gel electrophoresis methods. There was no TCR gene rearrangement detected in the colonic biopsy. Unfortunately, the patient died within 2 months of diagnosis. Copyright © 2011 John Wiley & Sons A/S.